Remaking the State from within: presidential control through bureaucratic redesign in Brazil’s Foreign Ministry (SciELO Preprints, 2026)
Why do presidents reorganize bureaucracies, and what political effects follow? This article examines how intra-ministerial bureaucratic redesign functions as a strategic tool of presidential control and agenda prioritization within Brazil’s Ministry of Foreign Affairs (MFA) from 1985 to 2020. Drawing on agency design and institutional change literature, the study argues that administrative reorganizations are not merely technocratic adjustments, but deliberate attempts by presidents to (i) embed thematic priorities into bureaucratic structures and (ii) expand control over high-leverage institutional arenas. We propose that organizational “choke points,” such as command hierarchies and thematic units, are particularly targeted for intervention. Using a mixed-methods approach that combines descriptive statistics, geospatial mapping, and qualitative case studies, we identify three distinct redesign logics: (1) political-control interventions, as illustrated by Collor’s tripartite fragmentation of the Secretary-General; (2) agenda expansion and ideational signaling, evident in the creation of thematic units and the expansion of diplomatic posts under Lula; and (3) symbolic reversal and institutional hollowing, marked by the dismantling of multilateral, climate, and human rights units under Bolsonaro. These processes generate long-term institutional consequences, including policy drift, conversion, and the erosion or consolidation of bureaucratic capacity. The findings contribute to debates on presidential governance by showing how even highly professionalized and insulated bureaucracies can be strategically reshaped through everyday administrative instruments.